Student Learning Outcomes for Biblical Studies in the Liberal Arts - Webster, Jane S. (Teaching theology and religion, 2012)
What is the role of biblical studies in a liberal arts curriculum? At the 2009 North American Society of Biblical Literature conference, a panel of seven Bible scholars provided brief analyses and arguments about the appropriate goals of teaching biblical studies in undergraduate contexts in this historical moment. They consider and critique the notion of specific Student Learning Outcomes or Objectives (SLOs) for courses about the Bible. In the process they address questions such as: what is the relative importance of “coverage” (biblical literacy, disciplinary knowledge and methods, and the historical creation of the biblical texts) versus modern and historical reception and uses of these texts? In their contributions, the authors analyze ways that a biblical studies course can develop the critical reading and writing skills that are the hallmark of undergraduate education. Some authors find these skills furthered by not bracketing from study the normative truth claims in the texts and instead strategically and critically encouraging the identity work and religious seeking associated with religious uses of these texts. Others call attention to the institutional and classroom power dynamics which inform and are constituted by the current student learning outcomes movement.